(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Crime prevention is an important aspect of maintaining law and order and stability in any State, including the Republic of Uzbekistan. In the context of political, economic and social reforms in the country, the problems of crime, especially among young people, corruption, drug trafficking and extremism, remain relevant. The purpose of this study is to analyze the state of the crime prevention system in Uzbekistan, identify problem areas and develop recommendations for improving existing methods and approaches. The research uses a comprehensive interdisciplinary approach, including methods of law, sociology, psychology and criminology, with an emphasis on the analysis of the legislative framework, the effectiveness of law enforcement agencies, as well as social and educational initiatives. It is expected that the results of the study will help to increase the effectiveness of crime prevention, improve the interaction of government agencies, public organizations and citizens, as well as contribute to strengthening the legal culture in the country.